ADVOCACY FOR THE USE OF WEBSITES TO IMPROVE RT/RW SERVICES FOR THE COMMUNITY - Salma Azzahra; Sany Wafi Maulidina; Bianca Natasha Natasha; Fachri Assyidiq Assyidiq; Muhammad Habib Nur Fadhillah (Politeknik STIA LAN Bandung, 2022)
In the growing digital era, information technology plays a very important role in local government services such as RT/RW. The use of a website is a potential solution to overcome obstacles in delivering information in a timely and efficient manner to the community. With a website, up-to-date information such as announcements, activity schedules, and news can be accessed by the community anytime and anywhere. In addition, two-way interaction between the community and the RT/RW is also possible through the comments feature and online form on the website, thus facilitating communication and accelerating responses to community needs. Thus, the use of the website as a modern and efficient service tool at the RT/RW level is expected to improve services and meet community needs.